Women, men and creativity in higher education sector – comparative studies of leading EU and ECE countries - Anna Zachorowska-Mazurkiewicz; Tomasz Sierotowicz (Journal of International Studies)
The focus in the article is on creativity in the higher education sector in terms of gender perspective. The question posed concerns the relation between women’s and men’s patent activities and R&D expenditures. The paper is based on the data from the European Patent Office, 1999-2013 concerning creative activities performed by women and men in the higher education sector. The paper looks into the dynamics of changes in terms of the number of women and men researchers, R&D personnel and inventors, and combines them with the changes in R&D expenditures in the higher education sector. The analysis is conducted for the two groups of leading EU countries in the light of their patent activities. The objective of this exercise is to present the correlation between R&D expenditures and women and men in the R&D sectors, comparing these two groups of the EU countries.